Research and mental health in the medical profession - Rojas Miliano, Cristhian Alexander (2020)
Research allows to acquire certain behaviors or aptitudes such as social skills, resilience, perseverance, etc. Furthermore, it reduces the risk of dissatisfaction with professional and / or academic achievements in medical students. For these reasons, research can have a positive impact on the mental health of those who practice it. It is proposed that research is a relevant variable to be evaluated as a protective factor for the appearance of some mental health problems in Peruvian doctors and medical students.